"DOES IT BUZZ?": IMAGE AND TEXT IN EDWARD LEAR'S LIMERICKS. Issue 4 (8th November 2017) - Hassett, Constance W.
Abstract : The limericks of Edward Lear (1812–1888) prompted a mid-Victorian craze that flourishes to this day. Gorgeously illustrated new limericks appear in a 2015 issue of Poetry magazine (Madrid), a five-line skewering of Stalin is tucked into a recent New York Times obituary (Grimes). The newly founded Edward Lear Society celebrates at the Knowsley estate, and the keeper of the Edward Lear website adds a new feature on Lear and Comics. The British Academy's Chatterton lecturer attends to Lear's birds, including the parrot that "seized" a man's nose and the raven that "danced a quadrille" (Bevis 39, 41) – Lear's first work, it must be remembered, was the magnificent Illustrations of the Family of Psittacidae, or Parrots (1832). Of course he is best known today as a writer of nonsense (Peck 15). The illustrated limerick, his lighthearted venture into a double genre, perennially raises questions among his admirers and scholars about the internal dynamics linking its components. Borrowing from recent discussions of various picture-poem combinations, one might call the illustrated limericks in A Book of Nonsense "picture-limericks" (Dilworth 42), "imagetexts" (Mitchell, Picture Theory 89), or "iconotexts" (Louvel). As the labels all suggest, the core issue is the proximity of two media and whether or how they converge.